If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 8x + -4x Reorder the terms: 7 + 5x = 8x + -4x Combine like terms: 8x + -4x = 4x 7 + 5x = 4x Solving 7 + 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 7 + 1x = 4x + -4x Combine like terms: 4x + -4x = 0 7 + 1x = 0 Add '-7' to each side of the equation. 7 + -7 + 1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 0 + -7 1x = 0 + -7 Combine like terms: 0 + -7 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 2(y+2)+y=19-2y+3 | | 6x+3x-7x+4=10 | | (3x-4)(3x+5)=0 | | 4.8*15=72 | | -4-7=x | | (1/2x+3)=125 | | 6x^2+4x-2=52 | | 4.8*15= | | 9x+2=8x+7 | | 3x+2y-5+3y-2x= | | 15x+2=7x+4 | | 18k^2-12k=2+4k^2 | | 3/5y=2/3y+9 | | 2x+3-x= | | ax-bx=15forx | | 19-21=x | | (a+bi)(6-7i)=53+9i | | 4x-8=2x-18 | | 5(x-3)=2x+2(x-5) | | 5/8(12+3x)=15 | | 33x+57=33x+61 | | -5(2n-3)-6=3(5n+1)-8 | | ax-bx=15 | | 7-2x=6x-30 | | 11x-21=5+7x | | -21+-15=x | | -9(8x)= | | 5x/8=6 | | (-5r^4s^2)(9s^3-7r+4)= | | 5(7x-6)-4=35x-34 | | (-5r^4)(s^2)(9s^3-7r+4)= | | 2x^-2/3x |